Effect of autologous adipose tissue-derived mesenchymal stem cells on neovascularization of artificial equine tendon lesions - Conze, Philipp; van Schie, Hans TM; Weeren, René van; Staszyk, Carsten; Conrad, Sabine; Skutella, Thomas; Hopster, Klaus; Rohn, Karl; Stadler, Peter; Geburek, Florian (Regenerative medicine, 2014)
Aims: To investigate whether autologous adipose tissue-derived mesenchymal stem cells (AT-MSCs) treatment of tendon lesions increases neovascularization during tendon healing. Materials & methods: A standardized surgical model was used to create lesions in both front limb superficial digital flexor tendons (SDFTs) of nine horses. Either AT-MSCs or control substance was injected intralesionally 2 weeks post-surgery. Color Doppler ultrasonography of SDFTs was performed at regular intervals. Horses were euthanized 22 weeks post-treatment and SDFTs were harvested for histology. Results: The color Doppler ultrasonography signal was significantly more extensive at 2 weeks post-treatment and the number of vessels counted on histologic slides was significantly higher at 22 weeks post-treatment in AT-MSC-treated SDFTs. Conclusion: Our findings indicate that AT-MSC treatment has a beneficial effect on neovascularization of healing tendons.
Gesehen am 20.10.2020